Spontaneous splenic rupture in a patient with chronic granulocytic leukemia - Miranda, Hector Vergara; Martínez Zarazúa, Raúl Omar; Hernandez Ramírez, Mayra Alexandra; Rodríguez Briseño, José Angel; Muñoz Maldonado, Gerardo Enrique (International Surgery Journal, 2021)
Spontaneous splenic rupture is a rare phenomenon that is not associated with trauma. The most common causes of splenic rupture are hematological diseases (30.3%), inflammatory diseases (20%), infectious diseases (27.3%), drugs (9.2%), mechanical disorders (6.8%), and unknown causes (6.4%). Spontaneous splenic rupture secondary to hematological malignancy is rare; in this group of patients, chronic granulocytic leukemia is the main cause. The mechanism of spontaneous splenic rupture is uncertain. Three mechanisms have been suggested: the mechanical effect of leukemia and its infiltration in the spleen, especially if the capsule is invaded; splenic infarction with subsequent subcapsular hemorrhage and rupture of the splenic capsule, and coagulation abnormalities.